Authorities and Procedures for Detecting Financial Violations : A Study in French Legislation - Mohsen, Saif; Qadori, Tagreed (Journal of Legal Sciences, 2023)
France attached great importance to public funds Article 15 of the Declaration on Human and Citizen's Rights (DDHC) stipulates that society has the right to hold any public official accountable for his or her administration. For that reason, the French legislature has established a body specialized in the control of public funds, which it calls the Court of Accounting. It has established the Court of Budget and Financial Discipline to assist it. The courts are run by judges who cannot be dismissed. The courts are also given jurisdiction, administrative jurisdiction and the role and purpose for which they have been assigned